Connotative Meaning of Uzbek Verbs: Evaluative, Emotive and Stylistic Components in Lexicographic and Literary Data (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Connotation is often treated as a secondary layer of meaning; however, in verb semantics it plays a central role in shaping evaluation, emotional colouring, and stylistic positioning. This paper investigates the connotative meaning of Uzbek verbs with particular attention to their evaluative, emotive, and stylistic components as reflected in lexicographic descriptions and literary usage. The study is based on qualitative analysis of verb entries drawn from the Uzbek Explanatory Dictionary and contextual examples extracted from classical and modern Uzbek prose, including works by Abdulla Qodiriy and O‘tkir Hoshimov. By examining near-synonym verb sets, the research demonstrates that connotative distinctions among Uzbek verbs are systematic and relatively stable, rather than incidental or contextually random. The findings show that evaluative judgement, emotional stance, and register are encoded in verb choice and significantly influence interpretation in discourse. The paper argues that connotative information should be treated as an integral part of verb semantics and more explicitly represented in lexicographic practice and literary analysis.